Analysis Glycol Losses On Gas Dehydration Unit PT X Field Z - Desi Kusrini, M.T. (JURNAL BHARA PETRO ENERGI, 2023)
Abstract The dehydration process gas is a process of separation of gas from the water content by mixing an absorbent for example glycol, in PT X field Z process of dehydration of gas using triethylene glycol to decrease Water content Minimum below 7 lb / mmscfd to be sold to consumers. The goal of the research is to determine the water content that is absorbed in the contactor, knowing the number of glycol loss and knowing the cause of glycol loss after experiencing the process of dehydration. Every dehydrated process using glycol is always there whose name is glycol losses either in reboiler or contactor, but the losses are classified normal or abnormal loss, losses can be either liters or percentage loss glycol lost. To determine how much glycol is missing during the dehydration process then we have to look for production data such as gas flow rate data, inlet water content and outlet water content contactor then moisture content data, and the last data from glycol like SG Glycol and purity glycol, later from the data is known calculation of circulation glycol and know the amount of glycol loss whether the normal loss or abnormal loss. The water content omitted is 32.49 lbs / h while the Glycol losses found in the above-normal state are 0.35% with the lowest amount of Glycol losses of 0.02 gal / MMSCF and the largest 0.091 gal / MMSCF and the cause of Glycol loss Include the number of the tray, time, surface area of absorption, flow speed, and the temperature that is in the reboiler or the regeneration of glycol. Keywords: Glycol losses, dehydration, Glycol, triethylene glycol, tray. Abstrak Proses Dehidrasi gas adalah suatu proses pemisahan gas dari kandungan air dengan cara mencampurkan suatu absorbent misalnya saja glycol, di PT X Lapangan Z proses dehidrasi gas menggunakan trietylene glycol untuk menurunkan kandungan air minimal di bawah 7 lb/mmscfd agar bisa dijual ke konsumen. Tujuan Penelitian ini adalah untuk menentukan kandungan air yang terserap di contactor, mengetahui jumlah glycol loss dan mengetahui penyebab glycol loss setelah mengalami proses dehidrasi. Setiap proses dehidrasi menggunkan glycol selalu ada yang namanya glycol losses baik itu di reboiler ataupun contactor, namun losses tersebut digolongkan loss normal atau upnormal, losses bisa berupa liter ataupun presentase loss glycol yang hilang. Untuk menentukan berapa banyak glycol yang hilang pada proses dehidrasi maka kita harus mencari data produksi seperti data flow rate gas, kadar air inlet dan kadar air outlet contaktor kemudian data kandungan uap air dan yang terakhir data dari glycol seperti SG glycol dan kemurnian glycol, nantinya dari data tersebut diketahui perhitungan sirkulasi glycol dan mengetahui jumlah glycol loss apakah normal loss atau upnormal loss.Kandungan air yang dihilangkan ialah 32,49 lbs/jam sedangkan Glycol losses yang ditemukan pada keadaan diatas normal ialah 0,35% dengan jumlah Glycol losses yang terendah sebesar 0,020 gal/MMSCF dan yang terbesar 0,091 gal/MMSCF dan penyebab Glycol loss meliputi jumlah tray, waktu, luas permukaan penyerapan, kecepatan alir dan suhu yang berada di reboiler atau saat regenerasi glycol. Kata kunci: Glycol losses, dehydration, Glycol, triethylene glycol, tray. Reference Arnold, Ken. 1999. “Surface Production Operations Design of Gas Handling Systems and  Facilities Volume 2.” .Gulf Publishing Company. GPSA. 2004. “Engineering Data Book” Oklahoma: Gas  Processors Suppliers Association. Stewart, Maurice. 2011. ”Gas Dehydration Field Manual”.  Amsterdam: Gulf Professional Publishing.